Relationship Between Manufacturing Strategy, Strategic Human Resource Management Practices Organizational Performance - Ibrahim, Hazril Izwar (2007)
This study examines the relationship between manufacturing strategy, strategic human resource management (SHRM) practices and organizational performance. This research attempts to investigate the significance of SHRM practices in a mediating role between manufacturing strategies such as cost, quality, flexibility and speed and organizational performance. The study also investigates the interaction between SHRM practices and organizational context variables and its' effect on organizational performance. The study employs multiple regression, structural equation modeling (SEM) and path analysis to measure the relationship between manufacturing strategy, SHRM practices and organizational performance in the first sequence of the conceptual framework. The study utilizes two-way ANOVA to test the effect of the interaction between SHRM practices and organizational context variables such as country of origin, firm size, firm age and union, on organizational performance. A total of one hundred and twenty-one (121) manufacturing firms in the electrical and electronic sector in Malaysia have participated in this study. The analysis of the findings indicates significant relationship between SHRM practices and organizational performance. The study also finds that quality and flexibility are significantly related to SHRM practices. The result indicates that only cost strategy significantly predicts organizational performance. The study has proven SHRM practices as significant in a mediating role in the relationship between cost, quality and speed and organizational performance. Finally, the result indicates that none of the interaction between SHRM practices and organizational context variables such as country of origin, firm size, firm age and union, have any significant effect on organizational performance. In conclusion, the study discovers that the implementation of SHRM practices is important in order for firms to achieve their operational objective. The study also finds that SHRM practices mediate the relationship between manufacturing strategies such as cost, quality and speed and organizational performance and the interaction between SHRM practices and organizational context variables have no significant effect on organizational performance.